2020
DOI: 10.1093/ajcp/aqaa115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Immunohistochemical Analysis of Mucinous Cystic Neoplasm of the Liver

Abstract: Objectives Mucinous cystic neoplasm of the liver is characterized by neoplastic mucinous and/or biliary epithelium surrounded by ovarian-type stroma. Immunohistochemical studies have shown that the ovarian-type stroma expresses estrogen receptor, suggesting potential hormonal responsiveness. The molecular biology of mucinous cystic neoplasm of the liver remains poorly studied. Methods Transcriptome sequencing and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
0
15
0
8
Order By: Relevance
“…Recently, our group showed that ovarian-type stroma in MCN of the liver expresses markers and enzymes of steroidogenesis raising the possibility that the stroma produces hormones locally. 20 The identification of expression of SF-1 in the current series raises the same possibility for MCN of the mesentery and retroperitoneum.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, our group showed that ovarian-type stroma in MCN of the liver expresses markers and enzymes of steroidogenesis raising the possibility that the stroma produces hormones locally. 20 The identification of expression of SF-1 in the current series raises the same possibility for MCN of the mesentery and retroperitoneum.…”
Section: Discussionmentioning
confidence: 54%
“…21 Others have suggested that MCN of the pancreas arises from aberrant migration of primordial germ cells into the embryologic dorsal mesentery which forms the neck and body of the pancreas en route to the ovaries. 22-24 In our prior work, 20 we raise the possibility that both hypotheses may be true and the primitive cells may migrate into the pancreas and contribute to the periductal fetal mesenchyme around developing pancreatic ducts. The identification of MCNs within the retroperitoneum and mesentery with this distribution wherein the tumors follow the route of the dorsal mesentery from the central retroperitoneum to the right iliac fossa adds support to the hypothesis that the origin of MCN is related to the dorsal mesentery.…”
Section: Discussionmentioning
confidence: 93%
“…Using immunohistochemistry, nuclear expression of β-catenin for OLS was observed for all MCN cases and all OLS sites. Several studies have suggested the activation of Wnt signaling pathway in OLS and its contribution to MCN development 15 17 . Sano et al have shown the activation of Wnt signaling pathway in OLS by introducing Wnt1 and KRAS G12D to the epithelial component in mice 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Sano et al have shown the activation of Wnt signaling pathway in OLS by introducing Wnt1 and KRAS G12D to the epithelial component in mice 15 . Fukushima et al have shown the overexpression of Wnt2B and secreted frizzled-related protein , a moderator of Wnt pathway in OLS 16 and Treek et al have shown the upregulation of Wnt and the Hedgehog pathway in OLS 17 . This is in line with our result that all OLS showed nuclear accumulation of β-catenin irrespective of cyst size or OLS site and suggests consistent activation of Wnt pathway for OLS.…”
Section: Discussionmentioning
confidence: 99%
“…Co-Expression of SATB2 and CK20 in Mucinous Ovarian Tumors staining is needed, tissue depletion will limit the number of staining that can be performed. Therefore, it is important to use immunohistochemical staining effectively to determine the origin site, without unnecessary staining to increase the hospital cost of patients (Van Treeck et al, 2020). While many immunostaining or different combinations of immunostaining have been studied previously, including CK7, CK20, villin, CDX2, PAX8 and ER, the coexpression of mucinous ovarian tumors SATB2 and CK20 and its association with tumor pathological classification and prognostic outcome have not been reported.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%